EKSTROFI KANDUNG KEMIH PADA BAYI PEREMPUAAN SEBUAH LAPORAN KASUS - Gede Prayudi, Nyoman (E-Jurnal Medika Udayana; vol 3 no 4 (2014):e-jurnal medika udayana, 2015)
Three days old newborn female child with supravesical fissure; one of exstrophy bladder variant which rare to found . Physical examination on abdominal region looks a reddish bladder and normal external genital. Plain photo abdomen shows opacity in the pelvic cavity to the below abdominal impress the bladder. The patients did not have surgical reconstruction because she got cardiac abnormalities in the form of classic TOF so that surgery was delayed until improved cardiac performance.
Keywords: Bladder extrophy, supravesical fissure, TOF, female